We need to find the values of the missing integers uisng factorization:
1.
We need to factor the trinomial.
First, look at the sign of the expression
The first sign = -
The second sign = +
Now, we need to square root the first term x² = √x² =x.
Then, we use the parentheses ( ) ()
We put the result of the square root
(x )(x)
Then, we use the first sign (in this case is -) in the first parentheses and the multiplication of both signs (in this case -*+ = -) in the second parentheses:
(x- )(x-)
Finally, we need to find both numbers that multiply by each other the result is 15 and they add up to 8
Hence;
3*5 = 15
5+3=8
So, the result of the factoring is:
(x-5)(x-3)
Where
(ax+b)(cx+d).
So d = -3
2.
First, we can factor finding their common term:
In this case, is 2x. Hence we can write the equation as:
Now, we have the form ax²+bx+c
Find the product of ac= (1)(-12)= -12
Then, find two factors of ac that have a sum equal to b :
Then:
2-6 = -4
Rewrite the trinomial:
Use the factor by grouping:
Using the given expression:
Therefore:
b=2
c=1
3.
We have an expression with the form ax²+bx+c.
First, find the product of ac:
ac= 6*4 =24
Find two products of ac that have a sum equal to b.
Factors/ products
(12)(2)= 24 / 12+2 = 14
Hence, we can rewrite the trinomial as:
Where a= 3 and d=4